Introduction of the beef fluid in Peru - Lastres, Juan B. (1951)
Edward Jenner (1749-1823), was a great English whom humanity owes the portentous discovery of anti-smallpox vaccine. The world celebrated the year 1949, the bicentennial of his birth while in his person paid tribute to England in the field of History of Medicine.